DRAWBACKS OF GTM METHOD IN LEARNING LANGUAGE AND TRANSITION TO THE RIGHT METHOD (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Today, under the problem-solving method we understood a creation of problematic situations and independent activity of learners for finding the solutions during organization of the lesson. As a result, students’ creative abilities developed. That is why, we are able to identify the right methods for students which really belongs to their own levels. In this article is about identifying drawbacks of GTM method and transition to right method.